Analisis Pemahaman dan Implementasi Nilai-nilai Multikulturalisme dalam Hadis Sebagai Landasan untuk Membangun Harmoni Sosial di Era Globalisasi - Marbun, Siti Kholidah (UIN Sumatera Utara Medan, 2023)
This research aims to analyze the understanding and implementation of multiculturalism values in the sayings of Prophet Muhammad (peace be upon him) as a foundation for building social harmony in the era of globalization. The research methodology used is a descriptive-analytical method, which involves collecting data from primary and secondary sources, followed by analyzing the collected data. Primary data is gathered from hadith collections related to multiculturalism, while secondary data is obtained from literature such as journals and books relevant to the topic under discussion. The results of this research indicate that the multiculturalism values analyzed by the author encompass three aspects: human equality, tolerance, and fair behavior within Human Rights. Additionally, there are efforts to enhance the understanding and implementation of multiculturalism values, such as through (1) education and religious understanding by integrating multicultural values into ethics and social interactions related to justice, unity, equal rights, tolerance, and mutual assistance, (2) interfaith dialogue that can be facilitated through the Bottom-Up Religious Harmony Forum (FKUB), involving religious figures and community members, (3) dissemination of positive information by providing character education to teach how to detect fake news and reduce the spread of fake news and hate speech in society, and (4) cross-cultural understanding that can be developed as an additional skill when adapting to a region, enabling communication and interaction with peers from different cultural backgrounds. However, the article also identifies several challenges, such as lack of religious understanding, religious fanaticism, structural injustice, and the rising extremism and intoleranceIn the era of globalization, where changes and complexities occur within society, the multiculturalism values present in the hadiths become increasingly important in building social harmony and maintaining interfaith coexistence. Therefore, the understanding and implementation of multiculturalism values within the hadiths need to be continually enhanced and disseminated to the entire community.